Political Relations: Political Identity and Social Media in Elections in Indonesia - Candra, Ade; Fauzi, Anwar; Rahmadhani, Marissa Laila (Universitas Muhammadiyah Makassar, 2023)
This research examines the role of social media in shaping political identity and political participation in contemporary Indonesia. Utilizing document analysis, the study explores how individuals and societal groups use social media as a tool to influence and participate in political discourse. The method employed in this research is qualitative descriptive. The findings reveal that social media facilitates a framework for personal action, enabling widespread participation in various political and social issues, and integrating personal lifestyle values into political dialogue. The study also pays attention to the challenges faced by political parties in Indonesia in attracting voters, especially the younger generation who are highly engaged with social media, in the lead-up to the 2024 simultaneous elections. Lastly, it is found that social media has deepened social interaction and information for the millennial generation, particularly during the Covid-19 pandemic, affecting their views on politics and religion. The conclusion of this research emphasizes the importance of social media in shaping the political landscape in Indonesia, providing significant insights into how digital technology affects political participation and social identity.